Response to Guinnane and Hoffman: Medieval Anti-Semitism, Weimar Social Capital, and the Rise of the Nazi Party: A Reconsideration - Nico Voigtländer; Hans-Joachim Voth (Center for Economic Studies and ifo Institute (CESifo), 2022)
Guinnane and Hoffman (subsequently GH) comment on two of our papers: Voigtländer and Voth: "Persecution Perpetuated" (2012, subsequently PP) and Satyanath, Voigtländer and Voth: Bowling for Fascism (2017, subsequently BF). They allege that our econometric results are fragile and depend on outliers in the state of Bavaria; that our results do not account for the role of institutional actors, and that we 'misinterpret' history. This brief response addresses these allegations and shows that i) GH's empirical criticisms are targeted at small subsets of our results; ii) use ad hoc, restrictive specifications – standard procedures to address GH's concerns about outliers actually confirm our results; iii) GH's conceptual critique is misguided and based on a misrepresentation of Weimar history, especially when it comes to the case of Bavaria. In sum, the empirical findings in PP and BF stand as in our original publications.
Keywords: 330